On Spray Modeling with Quadrature‐Based Moment Methods. Issue 1 (25th January 2021) - Pütz, Michele; Pollack, Martin; Hasse, Christian; Oevermann, Michael
Abstract: Spray modeling requires a proper representation of the dispersed phase and involves models for a variety of physical phenomena. On the population scale, a properly formulated population balance equation provides a complete statistical description of the particle system. However, in most cases the high dimensionality entails prohibitive computational costs. Quadrature‐based moment methods (QBMM) limit the description of particle populations to a set of only a few moments and thus considerably reduce computational complexity. In order to apply QBMM to sprays, models for many involved physical processes must be formulated consistently in the QBMM‐context. We study secondary droplet breakup with QBMM using a simple well‐established spray breakup model and simplified setups.